2021
DOI: 10.3390/ijerph182212063
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Experiences, Understandings, and Responses to COVID-19 in Low- and Middle-Income Countries: A Systematic Review of Qualitative and Ethnographic Studies

Abstract: (1) Background: COVID-19 disruptions offer researchers insight into how pandemics are at once biological and social threats, as communities struggle to construct meaning from novel challenges to their ontological status quo. Multiple epistemes, in which public health imperatives confront and negotiate locally derived knowledge and traditions, vie for legitimacy and agency, resulting in new cultural forms. (2) Methods: To investigate the context and construction of community responses, a systematic review of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 104 publications
(248 reference statements)
1
27
0
Order By: Relevance
“…These included notions that COVID-19 was a manufactured phenomenon to manipulate the insurance reimbursement system for additional profits from testing and treatment, and that COVID-19 tests are not trustworthy and misdiagnose and amplify case numbers without (symptomatic) evidence. This aligns with other studies in Indonesia and elsewhere which demonstrated that communities with low access to COVID-19 information, or expressing beliefs of disease causation which do not align with the dominant biomedical explanations often have low levels of trust and poor adherence to pandemic restrictions [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These included notions that COVID-19 was a manufactured phenomenon to manipulate the insurance reimbursement system for additional profits from testing and treatment, and that COVID-19 tests are not trustworthy and misdiagnose and amplify case numbers without (symptomatic) evidence. This aligns with other studies in Indonesia and elsewhere which demonstrated that communities with low access to COVID-19 information, or expressing beliefs of disease causation which do not align with the dominant biomedical explanations often have low levels of trust and poor adherence to pandemic restrictions [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 87%
“…As per HCP narratives, the community was suspicious of the dominant biomedical explanation for the phenomenon, evidenced by the fact that many community members have no empirical experience with sick patients despite nonadherence to preventive protocols. This suspicion and mistrust of health authorities have been reported elsewhere in the scholarly literature [40][41][42][43][44][45]. HCPs reported hearing rumours and second-hand information from the community expressing incorrect and conspiratorial beliefs about the origin and nature of COVID-19.…”
Section: Discussionmentioning
confidence: 77%
“…Child care is another important segment affected by the financial distress by COVID-19 ( Vance et al, 2021 ). The findings from Poland hint that the financial insecurity during COVID-19 and related psychological problems has resulted in the postponement of childbearing intentions ( Kaye et al, 2021 ; Malicka et al, 2021 ; Raymond and Ward, 2021 ).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Child care is another important segment affected by the financial distress by COVID-19 (Vance et al, 2021). The findings from Poland hint that the financial insecurity during COVID-19 and related psychological problems has resulted in the postponement of childbearing intentions (Kaye et al, 2021;Malicka et al, 2021;Raymond and Ward, 2021). The financial struggle among healthcare workers, especially the nursing staff has the opinion of better compensation during a pandemic due to their heavy workload (Akkuş et al, 2021;Cho et al, 2021).…”
Section: Financial Strugglesmentioning
confidence: 99%
“…But because healthcare systems serve communities, community capacities are equally important. This may include resource management and allocation [111]. However, while capacities are easily measured, focusing on them alone runs the risk of ignoring wider determinants and dependencies, and recent studies have highlighted the inadequacies of focusing on physical capacities in healthcare [71].…”
Section: Pre-event Themesmentioning
confidence: 99%